Nilai Ideologi Salafi dalam Buku al-‘Arabiyyah Baina Yadaik (Analisis Semiotika Roland Barthes) - Muhammad Yusuf (Hasanuddin University, 2022)
Internalization of the religious values ​​of the Arab community in Arabic textbooks is a common thing considering its capacity as part of the culture of the population. However, the ideology of the Arab community was considered incompatible with the religious climate in Indonesia. Al-’Arabiyyah Baina Yadaik is an Arabic textbook compiled by experts from Saudi Arabia. The textbook is widely used in the climate of Arabic language education in Indonesia. Ubaidillah believes that this book contains elements of Salafi values, therefore it needs to be filtered again. This study seeks to follow up on the above thesis. Roland Barthes' literary style and semiotic approach are methodological instruments in this study. The results of this study strengthen the thesis of Ubaidillah which states that the book Al-'Arabiyyah Baina Yadaik contains Salafi ideological values. Among the values ​​of the Salafi are the prohibition for a male teacher to teach female students and a female teacher from teaching male students, the prohibition for women to wear trousers, and the absolute law of polygamy.